Combined platelet-rich plasma and lipofilling treatment provides great improvement in facial skin-induced lesion regeneration for scleroderma patients - Francesco Virzì; Paola Bianca; Alessandro Giammona; Tiziana Apuzzo; Simone Di Franco; Laura Rosa Mangiapane; Maria Luisa Colorito; Dario Catalano; Emanuela Scavo; Annalisa Nicotra; Antonina Benfante; Giuseppe Pistone; et al. (Stem Cell Research & Therapy, 2017)
Abstract Background The use of stem cells, including mesenchymal stem cells (MSCs), for regenerative medicine is gaining interest for the clinical benefits so far obtained in patients. This study investigates the use of adipose autologous tissue in combination with platelet-rich plasma (PRP) to improve the clinical outcome of patients affected by systemic sclerosis (SSc). Methods Adipose-derived mesenchymal stem cells (AD-MSCs) and PRPs were purified from healthy donors and SSc patients. The multilineage differentiation potential of AD-MSCs and their genotypic–phenotypic features were investigated. A cytokine production profile was evaluated on AD-MSCs and PRPs from both healthy subjects and SSc patients. The adipose tissue-derived cell fraction, the so-called stromal vascular fraction (SVF), was coinjected with PRP in the perioral area of SSc patients. Results Histopathological and phenotypical analysis of adipose tissue from SSc patients revealed a disorganization of its distinct architecture coupled with an altered cell composition. Although AD-MSCs derived from SSc patients showed high multipotency, they failed to sustain a terminally differentiated progeny. Furthermore, SVFs derived from SSc patients differed from healthy donors in their MSC-like traits coupled with an aberrant cytokine production profile. Finally, the administration of PRP in combination with autologous SVF improved buccal’s rhyme, skin elasticity and vascularization for all of the SSc patients enrolled in this study. Conclusions This innovative regenerative therapy could be exploited for the treatment of chronic connective tissue diseases, including SSc.